Ethics and the economy. Issue 1 (2014) - ,
Abstract : Purpose – An examination of the economy reveals it to be structured in ways that contradict generally accepted ethical values. This is primarily due to the narrowness of its principles, being focused on the maximisation of monetary costs and benefits and on the separation of the economic realm from the realm of ethics. Economics now exists as an independent realm in which some crucial values can be routinely disregarded. The problematic nature of the economy is most apparent when issues of global sustainability and justice are considered. It is argued that these problems are systemic; they are inevitably generated by the structures built into the current economic theory and practice and cannot be remedied without fundamental system replacement. A radically alternative economy is sketched, in which institutions and practices enable and reward more satisfactory values. Implications for the economics profession are considered, notably to do with the lack of concern with the problems evident within economics. It is suggested that "virtue ethics" best enables thinking about this field. This paper seeks to discuss these issues.Design/methodology/approach – The paper is a critical theoretical discussion of the ethical implications of the economy. Thus, there is little to say about "methodology" other than that several aspects of conventional economic theory and practice are considered, and in general rejected.Findings – The paper rejects conventional economic theory and practice and points to the need for a radically alternative model.Originality/value – The author is not aware of work making the main points this paper raises, i.e. to do with the important connections with "The Simpler Way" perspective on sustainability and economics.